1999
DOI: 10.1068/a310647
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Boundaries: Vacancy Chains and the Evaluation of Urban Development Corporations

Abstract: Recent years have seen the establishment of numerous spatially bounded regeneration agencies in the United Kingdom, prominent amongst which have been urban development corporations (yDCs).Attempts to evaluate such agencies have so far focused almost exclusively upon the impacts within formally delimited areas and have neglected to consider the effects on surrounding nondesignated areas. In this paper, an attempt is made to address this by devising a technique for assessing the wider effects of spatially bounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…The trends in the change data could also reflect the 'lagged' effects of the regeneration initiatives that were rolled-out across the city-region during the 1990s and early 2000s (see the earlier 'case study' section). It was beyond the scope of this paper to evaluate the different impacts of these various interventions on deprived neighbourhoods in the city-region (instead see Robson et al, 1999;Squires, 2009;Turcu, 2012). However, research has suggested that regeneration efforts helped to enhance developer and investor confidence in deprived neighbourhoods at a time when urban policy was charged with delivering brownfield redevelopment alongside economic and social improvements in the most disadvantaged places, including Greater Manchester (see Schultz-Baing and Wong, 2012) viii .…”
Section: The Structure Of Deprived Neighbourhood Changementioning
confidence: 99%
“…The trends in the change data could also reflect the 'lagged' effects of the regeneration initiatives that were rolled-out across the city-region during the 1990s and early 2000s (see the earlier 'case study' section). It was beyond the scope of this paper to evaluate the different impacts of these various interventions on deprived neighbourhoods in the city-region (instead see Robson et al, 1999;Squires, 2009;Turcu, 2012). However, research has suggested that regeneration efforts helped to enhance developer and investor confidence in deprived neighbourhoods at a time when urban policy was charged with delivering brownfield redevelopment alongside economic and social improvements in the most disadvantaged places, including Greater Manchester (see Schultz-Baing and Wong, 2012) viii .…”
Section: The Structure Of Deprived Neighbourhood Changementioning
confidence: 99%
“…Figure 3 summarises the levels of LEDM funding (per 1,000 population) obtained by each council in Phase 2 in relation to the relative disadvantage experienced in its area. Relative disadvantage has been measured by the "Degree of Deprivation Index", developed by Robson et al (1994), which uses a number of indicators such as unemployment, income levels, dependency on social security benefits, health and housing stan- Figure 3 highlights how the allocation of the LEDM funding tended to favour more prosperous, eastern seaboard councils with a high rating capacity and comparatively low levels of deprivation. Only Belfast and Deny have high levels of deprivation and received the highest levels of funding (Quadrant 1), reflecting their importance as Northern Ireland's main cities.…”
Section: The Rationale For District Council Involvement In Local Economic Development Innimentioning
confidence: 99%
“…In the 1990s, when evaluating the Central Manchester Development Corporation, Bristol Development Corporation and Leeds Development Corporation, Robson et al (1998Robson et al ( , 1999 piloted a technique for helping to evaluate some of the effects of property-led regeneration. This consisted of tracing so-called vacancy chains as the supply of new property stimulated turnover among users of buildings.…”
Section: Introductionmentioning
confidence: 99%